Review of: Imaging Pilgrimage: Art as Embodied Experience by Kathryn R. Barush - Ian Rotherham (International Journal of Religious Tourism and Pilgrimage, 2022)
Book Review of Imaging Pilgrimage: Art as Embodied Experience by Kathryn R. Barush